Carbon nanofiber activated by molybdenum disulfide as an effective binder‐free composite anode for highly reversible lithium storage. (12th February 2020) - Wu, Manman; Liu, Cong; Sun, Rui; Yu, Tianjiao; Li, Yuhong; Yang, Gang
Summary: Carbon nanofiber film (CNF) as anode material for lithium‐ion batteries (LIBs) draws attention for its excellent cyclic stability, but its practical application is limited due to low specific capacity. Considering the advantages of pure CNF and MoS2, a flexible film which CNF covered by MoS2 (MoS2 /CNF) is successfully produced and evaluated as a binder‐free electrode for LIBs without mixing with carbon black and polymer binder. MoS2 nanoflakes (8.91 wt% of the composite sample) covering on CNF (MoS2 /CNF‐B sample) plays the key role in activating the electrochemical properties of CNF, but dense MoS2 nanoflakes (39.4 wt%) on CNF (MoS2 /CNF‐A) seriously limit the electrochemical properties of CNF. At 0.1 and 1.0 A g −1, MoS2 /CNF‐B sample delivers 967.1 and 605.7 mA h g −1, the capacities are almost twice as much as those of pure CNF. The initial columbic efficiency of MoS2 /CNF‐B sample of 76.4% is much higher than that of pure CNF sample of 62.1%. Moreover, MoS2 /CNF‐B sample presents no capacity decay till 100 cycles, and the cycled electrode at the 100th cycle still maintains a stable composite structure of MoS2 nanoflakes covering on CNF. Abstract : Taking the advantages of CNF and MoS2, CNF covered by MoS2 is successfully produced as binder‐free electrode for LIBs. MoS2 nanoflakes (8.91 wt% of the composite) covering on CNF (MoS2 /CNF‐B) plays the key role in activating the electrochemical properties of CNF. At 0.1 and 1.0 A g −1, MoS2 /CNF‐B delivers 967.1 and 605.7 mA h g −1, they are almost twice as much as those of pure CNF. MoS2 /CNF‐B presents no capacity decay till 100 cycles.